Low-Temperature Micro-PL Measurements of InAs Binary Quantum Dots on GaAs Substrate - Chit Swe, Nan Thidar; Suraprapapich, Suwaree; Wissawinthanon, Chanin; Panyakeow, Somsak; Tu, Charles W.; Arakawa, Yasuhiko (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2007)
Optical properties of InAs binary quantum dot (bi-QD) molecules grown on the (001) GaAs substrate were measured by means of temperature- and excitation-power-dependent photoluminescence (PL) spectroscopy. It was observed that the shape and peak position of the PL spectra changed with the temperature and with the excitation power. It was also found that the linear polarization degree of the bi-QD PL signal changed with temperature. The temperature-dependent PL described that the linear polarization degree of bi-QDs is closely related to the carrier dynamics.